The Benefits of Cloves Eugenol in Various Industries in Indonesia - TOWAHA, JUNIATY (Puslitbang Perkebunan, 2012)
Eugenol is a major component contained in oil of cloves (Syzygium aromaticum) with content about 70-96%.Â Eugenol contains several functional groups are allyl (-CH2-CH =CH2), phenol (-OH) and methoxy (-OCH3), so the presence of these groups can enable the synthesis of eugenol as a base for a variety of other compounds with higher value such as isoeugenol, eugenolacetate, isoeugenolacetate, benzyl eugenol, benzylisoeugenol, methyleugenol, eugenolmethyl-ether, eugenolethylether, isoeugenolmethylether, vanillin and so on. The eugenol and derivatives compounds that have a use in various industries, such as pharmaceuticals, cosmetics, food and beverages, cigarettes, pesticides,Â fishery, mining, active packaging and other chemical industries. Isolation processing of eugenol compound from cloves oil in Indonesia is still very limited, because of Indonesia as a main producer of clove oil the world is expected to increase the diversification ofÂ downstream industry which had a positive impact on economic growth in Indonesia. Therefore, the government needs to provide a conducive regulatory to the development of downstream industries such as easy investment, tax breaks and other conducive policies breakthrough such as technology transfer for UMKM scale industry. Keywords : Eugenol, clove (Syzygium aromaticum), agro industry, dawn-stream industry, small and medium interprises.